Pengaruh Pelaksanaan Terapi Spiritual Terhadap Kemampuan Pasien Mengontrol Perilaku Kekerasan - Ernawati, Ernawati; Samsualam, Samsualam; Suhermi, Suhermi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Nurses can control the violent behavior of patients by taking action, one of which is spiritual or religious therapy. The form of spiritual therapy in this study is dzikir and listening to the recitation of the Qur'an surah Ar-Rahman. This study aims to determine the effect of implementing spiritual therapy on the ability of patients to control violent behavior in the Walnuts Room of RSKD Dadi, South Sulawesi Province. The research design used in this study is the Pre Experimental One Group Pretest-Posttest Design method, namely the research design that has Pre-test before being given treatment and Post-test after being treated. The research instrument used observation sheets of signs and symptoms that appeared in patients before and after being given spiritual therapy. The sample was determined by using purposive sampling technique with a sample size of 20 patients. The influence test was carried out by using the Wilcoxon statistical test with a value of p <0.05. The results showed that there was a significant influence between the implementation of spiritual therapy on the ability of patients to control violent behavior wherein the results of the Wilcoxon test were obtained (p = 0.003) Î± <0.05. The average ability to control violent behavior before spiritual therapy is 9 patients while the average after doing spiritual therapy is as many as 11 patients. The conclusion of this study is that there is an influence between the implementation of spiritual therapy on the ability of patients to control violent behavior in the canary room of RSKD Dadi, South Sulawesi Province. It is expected for nurses to further increase the provision of spiritual therapy to the patient's ability to control violent behavior.